Enhanced Separation Concept (ESC): Removing the Functional Subunit from the Electrode by Molecular Design. Issue 31 (12th June 2019) - Brandl, Thomas; El Abbassi, Maria; Stefani, Davide; Frisenda, Riccardo; Harzmann, Gero D.; van der Zant, Herre S. J.; Mayor, Marcel
Abstract : A new concept to improve the reliability of functional single molecule junctions is presented using the E ‐field triggered switching of Fe II bis‐terpyridine complexes in a mechanically controlled break junction experiment as model system. The complexes comprise a push‐pull ligand sensing the applied E ‐field and the resulting distortion of the Fe II ligand field is expected to trigger a spin‐crossover event reflected in a sudden jump of the transport current. By molecular engineering, the active centre of the complex is separated from the gold electrodes in order to eliminate undesired side‐effects. Two aspects are considered to isolate the central metal ion, namely the spacing by introducing additional alkynes, and the steric shielding achieved by bulky isopropyl groups. With this small series of model complexes, a pronounced correlation is observed between the occurrence of bistable junctions and the extent of separation of the central metal ion, affirming the hypothesized Enhanced Separation Concept (ESC). Abstract : The reliability of single molecule switches is improved by better separating the molecule's functional subunit from the electrode surface. Both, increasing the spacing and insulation by bulky substituents contributed to increase the likeliness of spin cross‐over events in immobilized iron(II) terpyridine complexes.